PENGARUH STRESS DAN KEPEMIMPINAN TERHADAP KINERJA PERAWAT DI RUMAH SAKIT UMUM DAERAH PEMATANGSIANTAR - Muhammad Fauzan (Universitas Lambung Mangkurat, 2017)
This study aims to determine: (1) the effect of stress on the performance of nurses in the District General Hospital dr. Djasamen Saragih Pematangsiantar; (2) the effect of leadership on the performance of nurses in the District General Hospital dr. Djasamen Saragih Pematangsiantar; (3) the effect of stress and simultaneously on the leadership performance of nurses in the District General Hospital dr. Djasamen Saragih Pematangsiantar; (4) the most dominant variables affect the performance of the nurse at the General Hospital of dr. Djasamen Saragih Pematangsiantar. The population in this study were 114 respondents nurses Regional General Hospital dr. Djasamen Saragih Pematangsiantar and samples taken as many as 53 respondents with a passing stage cluster sampling and incidental sampling. The data used in this study are primary data and secondary data. Primary data is data obtained from the sample through field research by using questionnaires given directly to respondents that made the object of this research and secondary data is data obtained from the documentation or other information sources that can support the object under investigation. The data collection technique using a survey method to distribute a list of statements (questionnaire) directly to the Regional General Hospital nurses Djasamen Saragih Pematangsiantar and analysis techniques using multiple linear regression analysis. The results of this study concluded that: (1) stress a significant negative effect on the performance of nurses in the District General Hospital dr. Djasamen Saragih Pematangsiantar; (2) leadership positive effect on the performance of nurses in the District General Hospital dr. Djasamen Saragih Pematangsiantar; (3) The variables stress and leadership partially and simultaneously have a significant influence on the performance of nurses in the District General Hospital dr. Djasamen Saragih Pematangsiantar; (4) based on the results of testing, stress is the most dominant variable affecting the performance of nurses, when compared in leadership.